QUALITY OF HEALTH SERVICES IN THE HEALTH GONDANGREJO GONDANGREJO DISTRICT KARANGANYAR REGENCY - Liliek Winarni, Aris Tri Haryanto, Fitria Mar’atus Soliha (Solidaritas, 2018)
ABSTRACTÂ The purpove of this research is to know the level of quality of health service in the health Gondangrejo, Gondangrejo District, Karanganyar Regency. Researchers use research approach was qualitative. Qualitative methods are descriptive. Data types and sources of data that researchers use are primary data and secondary data with techniques of data and collecting through interviews to the patient and the medical officer at the health Gondangrejo, as well as survey directly to obtain the required data is data about how the quality of health services tn the health Gondangrejo. The method of collecting informants researchers use is purposive sampling with informan 1 person administrative sub division chair, 1 person nurse, 2 person midwife, 1 person chairman the ER, 1 person doctor, 1 officer and 18 man pharmacists patients.The results of research on the quality of health services in the health Gondangrejo, Gondangrejo District, Karanganyar Regency, measured using the 5 public service quality indicator : Tangibles, Reliability, Responsiveness, Assurance, and Empaty.The ministry of public health conducted by the gondangrejoâve been effective because it was getting a good asseaament indicators are used, this is indicated by the quote the results of interviews with researchers patients and some medical officer in the health Gondangrejo. These five indicators of the quality of service that has already been examined by researchers, based on the results of interviews indicate that the quality of health services provided is already â GOODâ and as expected by the patients.Â Keywords : Quality of service, Clinics, Qualitative